Exploring Spiroplasma Biology: Opportunities and Challenges - Harne, Shrikant; Gayathri, Pananghat; Béven, Laure (Frontiers in Microbiology, 2020)
Spiroplasmas are cell-wall deficient helical bacteria belonging to the class Mollicutes. Their ability to maintain a helical shape in the absence of cell wall and their motility in the absence of external appendages have attracted attention from the scientific community for a long time. In this review we compare and contrast motility, shape determination and cytokinesis mechanisms of Spiroplasma with those of other Mollicutes and cell-walled bacteria. The current models for rod-shape determination and cytokinesis in cell-walled bacteria propose a prominent role for the cell wall synthesis machinery. These models also involve the cooperation of the actin-like protein MreB and FtsZ, the bacterial homolog of tubulin. However the exact role of the cytoskeleton proteins is still under much debate. Spiroplasma possess MreBs, exhibit a rod-shape dependent helical morphology, and divide by an FtsZ dependent mechanism. Hence, spiroplasmas represent model organisms for deciphering the roles of MreBs and FtsZ in fundamental mechanisms of non-spherical shape determination and cytokinesis in bacteria, in the absence of a cell wall.